2002
DOI: 10.1002/hyp.1137
|View full text |Cite
|
Sign up to set email alerts
|

The concept of effective length in hillslopes: assessing the influence of climate and topography on the contributing areas of catchments

Abstract: Abstract:This paper introduces a concept of 'effective length' in hillslopes to define the effective area influencing the runoffproducing saturated zones of a hillslope or catchment. This effective area of a catchment usually is less than that given by its physical boundaries, particularly in regions where the total potential evaporation exceeds total rainfall on an annual basis. In this paper, expressions for effective lengths in hillslopes with different scale, shape and soil properties are derived for given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…As in other studies (Aryal et al, 2003;Beven, 1997) the results reported here suggest that runoff can be generated in a large area of the catchment, but its contribution to outflow from the catchment may be limited from various part of the catchment. However in addition to "effective slope length" (Aryal et al, 2003) or "dynamic contributing areas" (Beven, 1997), this can also be associated with a compensating effect of surface depressions in flat landscapes, when only "excess of runoff" generated within a depression under a single rainfall event can be passed down gradient.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As in other studies (Aryal et al, 2003;Beven, 1997) the results reported here suggest that runoff can be generated in a large area of the catchment, but its contribution to outflow from the catchment may be limited from various part of the catchment. However in addition to "effective slope length" (Aryal et al, 2003) or "dynamic contributing areas" (Beven, 1997), this can also be associated with a compensating effect of surface depressions in flat landscapes, when only "excess of runoff" generated within a depression under a single rainfall event can be passed down gradient.…”
Section: Discussionsupporting
confidence: 84%
“…However in addition to "effective slope length" (Aryal et al, 2003) or "dynamic contributing areas" (Beven, 1997), this can also be associated with a compensating effect of surface depressions in flat landscapes, when only "excess of runoff" generated within a depression under a single rainfall event can be passed down gradient. This also could be considered as extreme case or macro-scale of surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of length (Kinnell 2000, 2007, Rejman & Brodowski 2005, Bagarello & Ferro 2010 and slope gradient (Bracken & Kirkby 2005, Assouline & Ben-Hur 2006, Moreno de las Heras et al 2010) on soil loss and runoff were studied extensively, with the general conclusions that eroded materials and runoff increase with higher slope steepness (Young & Mutchler 1969a, Wischmeier & Smith 1978, Liu et al 1994, Gabriels 1999, Chaplot & Le Bissonnais 2003. Moreover, a clear reduction in runoff for each unit of slope length was observed as slope length increased (Gascuel Odoux et al 1996, Aryal et al 2003, Parsons et al 2006. However, few research has been conducted on the influence of slope shape on runoff and soil erosion.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are problems with the use of this term, including no constrained definition and the difficulty of quantifying it (Bracken and Cloke, 2007;Michaelides and Chappell, 2009 as active areas which actually connect to the river network. This has also been referred to as "effective hillslope length" (Aryal et al, 2003) and "dynamic contributing areas" (Beven, 1997). Therefore, landscape position is important as areas of the landscape closer to the river channel are more likely to connect.…”
Section: Management Of Hillslope-channel Connectivity and River Channmentioning
confidence: 99%